ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPANTENAGA KERJA DI PROVINSI JAWA TENGAH - , Muhammad Irfan Nur Aziz; , Drs. Yuni Prihadi Utomo, MM (2017)
This study aims to analyze the factors that affect employment in the province of Central Java. These factors include the GDP, inflation, government spending, and the minimum wage districts / cities. The data used in this research is secondary data, that is data of the labor force working in Central Java province, the inflation data, local government spending data, and the minimum wage data regencies / cities that are sourced from the Central Statistics Agency of Central Java Province. The analytical tool used in this research is multiple linear regression analysis, the analysis used to find the effect of several independent variables on the dependent variable. The results of this study indicate that the GDP, inflation, and positive bepengaruh local government spending on employment in the province of Central Java. While the minimum wage districts / cities have negative effect on employment.